Processibility of black garbage bag as a novel binder system in metal injection molding - Mustafa, Najwa (2012)
The issues to be highlighted here is to fundamentally evaluate the potential of using waste Garbage Bag from High Density Polyethylene (HDPE) as a backbone binder in Metal Injection Molding (MIM.) This is by the fact that the earth has tons of Garbage Bag disposed every day and researcher believes such waste can be converted into more beneficial industrial product. Thus this research investigates the potential uses of garbage bag as a novel binder system in metal injection molding. Stainless steel SS316L was used which is garbage bag (HDPE) and palm kernel acts as binder system. Feedstock with three composition 30%, 40% and 55% powder loading (PL) were injected by injection molding machine with several injection parameter were optimized such as injection temperature (A), barrel temperature (B), injection pressure (C) and Speed (D). The optimum parameter for highest green density, strength were optimized in Taguchi Method orthogonal Array L9 ( 3 ) and analysed by using Signal to Noise Ratio (S/N ratio).Results shows the optimum variables for 30% PL the highest density is A0, B2, C1 and D0 while for green strength are combination of A0, B0, C0, D1. For powder loading 40%, the optimize parameter for highest green part density are A2, B2, C0 and D2 and A0, B0, C1, and D0 for green strength. Besides, the highest green density for 0.55 PL by following the optimum variable are A2 , B2, C0 and D2 while for highest green strength are A2, B2, C2, and D2. Garbage bag are suitable acted as a binder system in metal injection molding. Furthermore, it could reduce the cost of binder system. The suitable volume ratios in mixing process produce a better feedstock in order to produce the green part by injection molding. Taguchi Method is among the best method in optimizing the injection variables as it can reduce the cost, time, improve accuracy and efficiency